The Utilization of Satellite Imagery for the Study of Settlement Development Trends - Syahar, Fitriana; Verliando, Weriza (Sumatra Journal of Disaster, Geography and Geography Education, 2021)
This study aims to see the development trend of the residential area in the City of Solok by using Landsat imagery and SPOT imagery through the processing of Geographic Information Systems and Remote Sensing. The type of research used is descriptive with a quantitative approach. The results of this study show that there have been nonincreasing residential areas by 656.02 hectares from 2009 to 2019 using Landsat imagery, and 122.26 hectares using SPOTimagery. The research was conducted using a weight edtiered supervised method and manual digitization to identify land use for settlements to determine the distribution of residential areas and the trend of settlement development in the city of Solok. The results of the distribution of settlement developments in Solok City where the Tanah Garam sub-district is the most dominant with an area of 234.63 hectares using Landsat imagery and 86.51 hectares using SPOT imagery.